Insight on the regulation mechanism of the nanochannels in hard and brittle materials induced by sparially shaped femtosecond laser - Kai, Lin; Chen, Caiyi; Lu, Yu; Meng, Yizhao; Liu, Yi; Cheng, Yang; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Chemistry, 2022)
The efficient fabrication of nanochannels on hard and brittle materials is a difficult task in the field of micro and nano processing. We have realized nanochannel arrays on silica with characteristic scales varying from 50-230 nm using a single femtosecond Bessel beam pulse of 515 nm. By characterizing the surface openings, we found that the characteristic scales of the nanopore openings are inextricably linked to the surface energy deposition effect. We achieved not only three asymmetric channel profiles by adjusting the laser-sample interaction region, but also high aspect ratio nanochannels with characteristic scales about 50 nm and aspect ratios over 100. These results on hard and brittle materials provide a broader platform and application scenarios for smart particle rectifiers, DNA molecular sequencing, biosensors and nanofluidic devices, which are also more suitable for future practical applications due to their low cost, good durability and high productivity.